Swimming characteristics of gyrotactic microorganisms in low-Reynolds-number flow: Chlamydomonas reinhardtii - Chen, Xiao; Zeng, Li; Wu, Yihong; Gao, Yunhua; Zhao, Yijun (Energy, ecology and environment (Online), 2017)
The swimming characteristics of gyrotactic microorganisms are significant to understand the ecological activities in lakes, rivers and oceans. The swimming velocity of a typical motile microorganism, Chlamydomonas reinhardtii , was measured for both still water and low-Reynolds-number flow, based on a microfluidic system. Results show that the swimming speed is subject to Gaussian distribution for the still water, and corresponding mean swimming speed is 41 μm/s. The streamwise mean swimming velocity, 35 μm/s, in the moving water is slightly less than that in the still water. It is also shown that the swimming direction in the horizontal plane is dominated by cell randomness for the still water, and 80% of the cells are aligned with the ambient flow when the flow velocity exceeds 333 μm/s. The standard deviation of swimming direction and the percent of swimming direction in the streamwise direction can reach a stable status with the increase of the flow velocity.